Cooperative Microactuator Systems - Kohl, Manfred; Seelecke, Stefan; Wallrabe, Ulrike (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue collects emerging research activities in the field of cooperative microactuator systems, which are expected to generate new synergies, e.g., through parallelization, cascading, and multistability, as well as through inherent sensing.